Digital detection of steppe vegetation change over time in Naâma (Algeria), using the soil-adjusted vegetation index - Belabbes, Ishak; Si Tayeb, Tayeb (Biodiversity: Research and Conservation, 2025)
Remote sensing has allowed us to analyse changes in land use over 42 years in a steppe zone located in south-western Algeria, covering most of Naâma Province (wilaya) and the western part of El Bayadh Province. The main economic activity is pastoralism there. The society faces many challenges, including complex social and environmental interactions, climatic factors, and anthropogenic actions that cause major degradation of the natural ecosystems, leading to desertification and erosion. Our spatio-temporal study of plant cover dynamics was conducted using 4-period Landsat scenes (1977-1987, 1987-1998, 1998-2008, and 2008-2019). The soil-adjusted vegetation index (SAVI) images were classified into 3 classes to detect changes in land cover. The results show varying degradation of steppe vegetation, as the plant cover decreased from 4.37% in 1977 to only 0.20% in 1987, followed by an increase to 8.80% in 1998, a decline to 1.05% in 2008, and a rise to 3.89% in 2019. Restoration measures should be taken in the areas classified as sensitive to desertification by using remote sensing.